The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.2139/ssrn.1160170
|View full text |Cite
|
Sign up to set email alerts
|

The Currency of Reciprocity - Gift-Exchange in the Workplace

Abstract: What determines reciprocity in employment relations? We conducted a controlled field experiment to measure the extent to which monetary and non-monetary gifts affect workers' performance. We find that non-monetary gifts have a much stronger impact than monetary gifts of equivalent value. We also observe that when workers are offered the choice, they prefer receiving money but reciprocate as if they received a non-monetary gift. This result is consistent with the common saying, "it's the thought that counts". W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
213
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(233 citation statements)
references
References 43 publications
(35 reference statements)
15
213
1
4
Order By: Relevance
“…Our prediction that symbolic gifts (such as good personal contact) rather than wages are a manager's main means of exchange in the field is also well in line with survey evidence by Campbell and Kamlani (1997) and Bewley (1999) on the determinants of worker's morale, as well as with empirical work showing that firms with bad management-worker relationships are penalized in that they need to pay higher wages to attract and retain workers (e.g., Borzaga and Depedri 2005). Lastly, a recent field experiment complemented by a questionnaire study by Kube, Maréchal, and Puppe (2008) finds that a gift-in-kind is significantly more likely to signal kind intentions than a wage increase, and-in contrast to a wage increase-significantly increases worker's productivity.…”
Section: Introductionsupporting
confidence: 78%
“…Our prediction that symbolic gifts (such as good personal contact) rather than wages are a manager's main means of exchange in the field is also well in line with survey evidence by Campbell and Kamlani (1997) and Bewley (1999) on the determinants of worker's morale, as well as with empirical work showing that firms with bad management-worker relationships are penalized in that they need to pay higher wages to attract and retain workers (e.g., Borzaga and Depedri 2005). Lastly, a recent field experiment complemented by a questionnaire study by Kube, Maréchal, and Puppe (2008) finds that a gift-in-kind is significantly more likely to signal kind intentions than a wage increase, and-in contrast to a wage increase-significantly increases worker's productivity.…”
Section: Introductionsupporting
confidence: 78%
“…Indeed, recent field experiments showed that positive reciprocity does not always survive outside the laboratory (Al-Ubaydli et al, 2015; U. Gneezy & List, 2006;Kube et al, 2012;Kube, Maréchal, & Puppe, 2013). In particular, the existence of a positive wage-effort relation in actual employment relationships seems to depend on two crucial conditions which are not necessarily given in the present setting: First, only if explicit cost and surplus information are provided, allowing employees to calculate their employer's surplus from the work contract, do workers have a reference point for being reciprocal (Hennig- Schmidt et al, 2010).…”
Section: Behavioral Predictionsmentioning
confidence: 99%
“…16 An explanation of a tournament's competitiveness index is provided at: http://www.owgr.com/about 17 Note that for the 2004 and 2006 Ryder Cup editions, the same tournament is played three times rather than two. 18 The objective of our study and the design of our empirical models are not intended to establish a comparison between monetary and nonmonetary incentives (see Kube, Marechal, & Puppe, 2012 for a comparison of the effect of monetary and nonmonetary rewards on the performance of a task). However, we see the value of providing the magnitude of monetary incentives to establish an informal comparison between the two.…”
Section: N O T E Smentioning
confidence: 99%